Evaluation of tolerance to alkaline media isolates tannery effluent - Alcarraz Curi, Mario (2013)
Industrial effluents biological treatment has obtained great important, becoming essent ial in the management of effluents, but for this, requires trained microorganisms adapted to the physicochemical condit ions of the effluent, so it is necessary to characterize effluents previously to design the t ype and treatment condit ions. Tanner y effluents of the plant, where the research was conducted, have pH within alkaline range and high BOD (Biochemical Oxygen Demand) indicating abundance of organic matter. These features led to the search for microorganisms tolerant to alkaline conditions for a potential treatment of these effluents. Culture media were designed based condit ioners tannery effluents at different pH values: 9, 10, 11 and 12.Of the 39 isolates, 100% grew in pH 9 and 10; 79.5% at pH 11; and 77% at pH 12. It should be noted that from the total strains tested, two (N3D and N4E) developed in all alkaline conditions experienced, with a positive tests for proteolysis and lipólisis simultaneously. The conclusion is that there are tannery effluent microorganisms wit h adaptive capacit y to environmental condit ions and with high potential for bioconversion of organic matter, characterist ics required for the treatment of effluents. The ability of these organisms for the production of alkaline proteases and lipases is another feature to be considered for multiple applications.